OVERVIEW PRESCRIBING WITH DUPLICATED NSAID THERAPY WITHOUT GASTRIC PROTECTIVE AGENTS AT A HOSPITAL IN INDONESIA - Nurmesa, Adi; Rachman, Abu; Jannah, Wardatul (Faculty of Mathematic and Natural Science, Garut University, 2024)
Pain is a defence mechanism for the body that arises when the tissues in the body are being damaged. Pain therapy can be used in the form of NSAIDs. In prescribing NSAIDs, there is a risk of drug-related problems in the form of treatment duplication without gastroprotective. This study aims to determine the description of the type of duplication of NSAIDs without gastroprotective and explain pharmacist intervention efforts in reducing drug-related problems in prescribing NSAIDs. This retrospective observational study is conducted on all incoming prescriptions at the pharmacy satellite in March-June 2022 at one of the hospitals in Indonesia. The results of this study found 53 cases of duplication of NSAID therapy without gastroprotective from a total of 3,200 prescriptions, with the most duplication of NSAID therapy between Ibuprofen 400 mg and Mefenamic Acid 500 mg 24 cases. Pharmacist intervention in the form of clinical prescription screening is beneficial to avoid the risk of drug-related problems in prescribing NSAIDs.